KONSEP FENOMENOLOGI SEBAGAI METODE DALAM MENGUNGKAP SETING PERILAKU PENGGUNA - Muhammad Rusdin Jumurdin; Erfin Kurniawan; Nurul Chairunnisa Noor (Yayasan Nusantara Hasana Berdikari, 2024)
Hospitals become public service buildings that bring together various individuals with diverse characteristics. Therefore, the activities that occur in it will produce various kinds of stigmas or points of view from its users depending on how and from what point of view they see and interpret the activities. This study aims to explore how user behavior settings are formed in a physical setting in a hospital using a phenomenological approach that is presented in a narrative manner. The results of the study using case samples involving childbirth activities concluded that the use of the phenomenological method is very supportive in exploring how users interpret their experiences that occur in a subject in a physical setting until it ultimately affects their stigma or psychology.